Hambatan Sosial Budaya Dalam Pembauran Masyarakat Tionghoa Dengan Masyarakat Lokal - Winarta, Frans Hendra (LAW REVIEW, 2004)
More than twenty discriminatory laws and regulations are still in force, some of them dating from the Dutch colonial administration, many of them from early years of Soeharto s New Order government. Some of them are: 1. "Policy for Resolving the Chinese Issue", Cabinet Presidium Instruction No. 37/V/IN/6/1967; 2. Presidential Instruction No. 14/1967 on "Chinese Religion, Beliefs, and Traditions "; 3. Home Affairs Ministry No. 455.2-360/1968 on "Regulation of Temples "; 4. Circular of Director General for Press and Graphics Guidance in the Ministry of Information No. 02/SE/Ditjen-PPGK/1998 on "Banning the Publication and Printing of Writings and Advertisements in Chinese Characters or the Chinese Language"; 5. Instruction of the Ministry of Home Affairs No. XOI/1997 on "Implementing Instructions for Population Registration " and the confidential instruction No. 3.462/1/755.6 of the Jakarta government dated January 28, 1980 both authorized special codes to be put on identification cards indicating ethnic Chinese origin; 6. Cabinet Presidium Circular SE-06/Pres-Kab/6/1967 on "Changing the Term China and Chinese " obliges Indonesians to drop the use of the term "Tionghoa " (as ethnic Chinese refer to themselves) and replace it with the term "china" (then a derogatory term). (http://www. hrw. org/reports98/indonesia3/discriminate, html) The discriminatory laws and regulations are in fact oppressing the life of Chinese ethnic custom in Indonesia. It is against human rights, especially cultural rights.